2001
DOI: 10.1055/s-2001-15789
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes After ARDS

Abstract: Early reports of late outcomes among survivors of ARDS indicated that most patients improved dramatically after their intensive care unit stay, and few lived with residua of their once-severe pulmonary injury. Over the last decade, a collection of new studies with improved methodology and novel questions has improved our understanding of life after ARDS. After reviewing these newer investigations in the context of previously published literature, we have drawn several preliminary conclusions: (1) Long-term sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…In studies among survivors of ARDS, it is known that nearly all of the patients are symptomatic at hospital discharge, but there is significant improvement over the first year after ARDS in most patients. 11 In addition, survivors of ARDS are also much less symptomatic than other patients with chronic lung disease. 11 Nonetheless, the mean activity score of our patients measuring disturbances to their daily physical activity and their mean impacts score covering a wide range of disturbances of psychosocial function remain significantly worse compared with those in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies among survivors of ARDS, it is known that nearly all of the patients are symptomatic at hospital discharge, but there is significant improvement over the first year after ARDS in most patients. 11 In addition, survivors of ARDS are also much less symptomatic than other patients with chronic lung disease. 11 Nonetheless, the mean activity score of our patients measuring disturbances to their daily physical activity and their mean impacts score covering a wide range of disturbances of psychosocial function remain significantly worse compared with those in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [3][4][5][6][7][8][9] have reported persistent symptoms, as well as radiologic and functional abnormalities during follow-up several weeks or months after hospital discharge, but the prevalence and severity of the longterm sequelae of SARS remain largely unknown. Because lung function is known to improve for up to 1 year after discharge from the hospital in survivors of other causes of acute lung injury, 10,11 it is imperative that long-term studies of SARS survivors be conducted in order to determine the persistence of abnormalities in pulmonary function, and whether these abnormalities contribute to permanent impairment and disability. As the majority of patients with SARS survive the illness 2 and medical personnel, physicians, nurses, and hospital workers are among those commonly infected in most countries, 2 an additional requisite for the identification and quantification of morbidity among survivors may be for the consideration of awarding compensation.…”
mentioning
confidence: 99%
“…In turn, these impairments affect the survivors' overall quality of life (QOL) [8, 9]. Previous studies also suggested that long-term survival is unaffected by ARDS status; however, ARDS severely affects QOL, functional independence, and cognitive function [1012]. In relatively healthy patients bearing few underlying diseases, severe pneumonia with ARDS status rarely occurs; however, patients that are relatively young and healthy when they develop ARDS may never recover completely and may experience ongoing functional limitations after an episode of critical illness [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to ARDS, studies have demonstrated reductions in health status for patients with other critical illnesses requiring prolonged mechanical ventilation, [23] with permission including sepsis [28], multiple organ dysfunction [29], and general ICU patients [17,30,31]. Although results vary, these studies also suggest decrements in a wide range of the domains of health status.…”
Section: Health-related Quality Of Lifementioning
confidence: 92%
“…These reports are limited to case series and prospective studies of patients recovering from ARDS. A review of 85 cases found that 19% of patients had persistent radiographic abnormalities at 3 or more months after extubation; the most common findings were bibasilar interstitial infiltrates and reticular changes [23]. In Herridge's et al follow-up study of over 100 ARDS survivors, 20% of patients had radiographic abnormalities at 1 year, with findings of linear fibrosis, small bullous cysts, and isolated areas of pleural thickening [19].…”
Section: Thoracic Imagingmentioning
confidence: 97%